α-SNAP Interferes with the Zippering of the SNARE Protein Membrane Fusion Machinery - Park, Yongsoo (American Society for Biochemistry and Molecular Biology, 2014)
Neuronal exocytosis is mediated by soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins. Before fusion, SNARE proteins form complexes bridging the membrane followed by assembly toward the C-terminal membrane anchors, thus initiating membrane fusion. After fusion, the SNARE complex is disassembled by the AAA-ATPase N-ethylmaleimide-sensitive factor that requires the cofactor α-SNAP to first bind to the assembled SNARE complex. Using chromaffin granules and liposomes we now show that α-SNAP on its own interferes with the zippering of membrane-anchored SNARE complexes midway through the zippering reaction, arresting SNAREs in a partially assembled trans-complex and preventing fusion. Intriguingly, the interference does not result in an inhibitory effect on synaptic vesicles, suggesting that membrane properties also influence the final outcome of α-SNAP interference with SNARE zippering. We suggest that binding of α-SNAP to the SNARE complex affects the ability of the SNARE complex to harness energy or transmit force to the membrane.